Nutritional condition among Children less than 5 years old in AL- Najaf City - Hatef Hedawi, Yasser; Hatim Ajeel, Sarah (International Journal of Psychosocial Rehabilitation, 2020)
Background A good nutrition is an essential component of good health. Malnutrition is known contributing factors to diseases and death. In the developing world, malnutrition affects approximately 800 million people, greater than 340 million whom are children under the age of five years. Over six million of those children die every year from malnutrition (2). Objectives: The study aims at assess the domains of nutritional status in term of (weight and height for age) through anthropometric measurements. Methodology: A descriptive / Cross-sectional study is conducted throughout the period of October 1st 2019 to June 17th 2020 in order to nutritional status for children less than 5 years old in AL-najaf city in terms of (weight and height for age) through anthropometric measurements. And also, to find out the relationships between child’s and mother’s demographic characteristics and nutritional status. A non-probability convenience sample of (1000) children with their mothers visiting the primary health care centers. This sample is distributed throughout two primary health care sectors according to Najaf Health Directorate. A total of (10) primary health care centers is selected for the purpose of the study. A pilot study was conducted and the questionnaire validity was achieved through a panel of (17) experts. Results: The majority of children were normal with assessed regard the nutritional status by weight for age indicators, as well as, nutritional status assessed through height for age and weight for height nutritional indicators. Some socio-demographic characteristics influenced children nutritional status, especially the mother educational, level economic status of the family and breast feeding. Conclusions: The majority of study sample recorded normal nutritional status according to all three nutritional indicators; weight for age (WAZ), weight for height (WHZ), and height for age (HAZ). Recommendations: Nutrition counseling and education to the mothers is an important component on health services which would help to decrease the effect of ignorance and faulty cooking or dietary practices. As well as proper feeding, home health care, food preparation, hygiene.